Free amino acids of Tronchuda Cabbage (Brassica oleracea L. Var. costata DC): influence of leaf position (internal or external) and collection time - Oliveira, Andreia P. (2008)
The free amino acid profile of 18 samples of tronchuda cabbage (Brassica oleracea L. var. costata DC) leaves, harvested at three different months, was determined by HPLC/UV−vis. The tronchuda cabbage leaves total free amino acid content varied from 3.3 to 14.4 g/kg fresh weight. Generally, arginine was the major compound, followed by proline, threonine, glutamine, cysteine, and glutamic acid. This study indicates that free amino acids are not similarly distributed: in external leaves, proline and arginine were the major free amino acids, while in internal ones, arginine was the main free amino acid, followed by threonine, glutamine, and cysteine. Significant differences were observed for valine, proline, arginine, leucine, cysteine, lysine, histidine, and tyrosine contents. The levels of some free amino acids were significantly affected by the collection period. In external leaves, this occurred with glutamic acid, serine, valine, leucine, cysteine, and ornithine contents, while in internal leaves, it occurred with aspartic acid, arginine, and total contents.